ANÁLISE COMPARATIVA DOS REQUISITOS DO ABNT ISO/IEC GUIA 58 E DA ISO/IEC 17011: Proposta de Modelo - Soares, Mauricio Araujo (2004)
In this exploratory research a comparative analysis of the requirements of the ABNT ISO/IEC Guide 58:1993 and of the Final Draft Standard ISO/IEC FDIS 17011:2004, which will replace the Guide, is performed . This analysis also takes into account the requirements of mutual recognition arrangements maintained by regional and international co-operations laboratory accreditation bodies. The present study discusses the critical issues in the changes of the requirements, as well as identifies all the differences between the two documents. The differences identified were used to put together a model for the diagnosis of adequacy of a laboratory accreditation system to the new requirements of the future ISO/IEC 17011. In order to verify the applicability of the proposed model, a case study was performed at the General Coordination for Accreditation (CGCRE) of the National Institute of Metrology, Standardization and Industrial Quality (INMETRO) which allowed for the identification of points for improvement of the proposed model as well as provided information aiming at facilitating the implementation of the ISO/IEC 17011 by CGCRE, when the standards is approved